[18F]-Fludarabine for Hematological Malignancies - Barré, Louisa; Hovhannisyan, Narinée; Bodet-Milin, Caroline; Kraeber-Bodéré, Françoise; Damaj, Gandhi (Frontiers in Medicine, 2019)
With the emergence of PET/CT using 18F-FDG, molecular imaging has become the reference for lymphoma lesion detection, tumor staging, and response assessment. According to the response in some lymphoma subtypes it has also been utilized for prognostication of disease. Although 18F-FDG has proved useful in the management of patients with lymphoma, the specificity of 18F-FDG uptake has been critically questioned, and is not without flaws. Its dependence on glucose metabolism, which may indiscriminately increase in benign conditions, can affect the 18F-FDG uptake in tumors and may explain the causes of false-positive imaging data. Considering these drawbacks, 18F-fludarabine, an adenine nucleoside analog, was developed as a novel PET imaging probe. An efficient and fully automated radiosynthesis has been implemented and, subsequently preclinical studies in xenograft murine models of hematological maligancies (follicular lymphoma, CNS lymphoma, multiple myeloma) were conducted with this novel PET probe in parallel with 18F-FDG. The results demonstrated several crucial points: tumor-specific targeting, weaker uptake in inflammatory processes, stronger correlation between quantitative values extracted from [18]F-fludarabine and histology when compared to 18F-FDG-PET, robustness during immunotherapy with rituximab, divergent responses between CNS lymphoma and glioblastoma (GBM). All these favorable findings permitted to establish a “first in man” study where 10 patients were enrolled. In DLBCL patients, increased uptake was observed in sites considered abnormal by CT and [18F]FDG; in two patients discrepancies were observed in comparison with 18F-FDG. In CLL patients, the uptake coincided with sites expected to be involved and displayed a significant uptake in hematopoietic bone marrow. No uptake was observed, whatever the disease group, in the cardiac muscle and brain. Moreover, its mean effective dose was below the effective dose reported for 18F-FDG. These preclinical and clinical findings revealed a marked specificity of 18F-fludarabine for lymphoma tissues. Furthermore, it might well be a robust tool for correctly quantifying the disease, in the presence of confounding inflammatory processes, thus avoiding false-positive results, and an innovative approach for imaging hematological malignancies.